Variability of Durable and Nondurable Consumption: Evidence for Six O.E.C.D. Countries - Gali, Jordi (The Review of Economics and Statistics, 1993)
The author estimates consumption variability ratios for both durable and nondurable consumption using data for six OECD countries. His methodology, which relies on a long-run restriction implied by the consumer's intertemporal budget constraint, overcomes many of the problems inherent to previous approaches. Some important departures from the permanent income model emerge: (1) nondurable consumption shows mild excess smoothness in the United States and Italy, and mild excess volatility in Japan and France, and (2) durable consumption shows extreme excess smoothness in all countries. Alternative factors capable of generating the differences in volatility across types of goods are discussed. Copyright 1993 by MIT Press.